Sleep apnoea among Australian Aboriginal and non-Aboriginal patients in the Northern Territory of Australia—a comparative study - Heraganahally, Subash S; Kruavit, Anuk; Oguoma, Victor M; Gokula, Chandran; Mehra, Sumit; Judge, Daniel; Sajkov, Dimitar (Sleep (New York, N.Y.), 2020)
Abstract Australian Aboriginal and Torres Straight Islanders (ATSI) are noted to have a higher burden of chronic health conditions. However, there is a paucity of data on obstructive sleep apnoea (OSA) in this population. In this retrospective study, we evaluated the clinical and polysomnographic (PSG) characteristics of ATSI and non-ATSI adult patients who underwent diagnostic PSG between 2011 and 2015. There were a total of 3078 patients. Of the total, 403 (13%) were of ATSI origin. Among those of ATSI origin, 61% were male and 39% females, while among the non-ATSI cohort, 66% were males. The median age was 47.8 years in ATSI and 51.5 years in the non-ATSI cohort. In the combined cohort, body mass index was more than 30 kg/m2 (61%), hypertension (14.4%), diabetes (17.8%), and heart disease (23.3%). The ATSI patients had higher rates of class III obesity (27 vs. 15%), hypertension (26 vs. 14%), cardiac disease (34 vs. 23%), and diabetes (37 vs. 17%). Among all the study participants, the PSG confirmed 83.7% of the patients had an apnoea–hypopnea index (AHI) more than 5/h, mild (AHI 5–15/h) in 28.4%, moderate (AHI 15–30/h) in 22.3%, and severe (AHI > 30/h) in 33.0%. Among the ATSI patients, 46% had severe OSA. The median total AHI value was higher in the ATSI population (25, interquartile range [IQR]: 11–58) compared to the non-ATSI (17, IQR: 7–36), and in rural/remote population (19, IQR: 8–42) compared to urban (17, IQR: 7–37). This trend was similar for NREM (non-rapid eye movement)-AHI and REM (rapid eye movement)-AHI scores, although statistically significant difference was found only with ATSI status. In the combined cohort the probability of (OR = 1.62, 95% CI: 1.32–2.00, p < 0.001) of severe OSA was 62% higher in individual with hypertension, however, when stratified by ATSI status, the association was only significant in the non-ATSI population (OR = 1.53 95% CI: 1.21–1.94, p < 0.001). The odds of severe AHI was also significantly associated with heart disease (1.37; 95% CI: 1.14,1.63, p < 0.001), diabetes (1.74; 95% CI: 1.43,2.10; p < 0.001) and smoking (1.28; 95% CI: 1.09,1.50, p = 0.0023) in the overall study cohort. In both ATSI and non-ATSI patients, body mass index, neck circumference, sleep efficiency, wake after sleep onset, and respiratory arousal index were significantly higher and independently associated with severe AHI.